KPP Tegallega Bandung's Individual Taxpayer Compliance: The Impact of Tax Administration Modernization, Tax Knowledge, and Tax Sanctions - Aisyah Ananda Putri; Wajib Ginting (eCo-Buss, 2024)
This research aims to evaluate how company image, service quality, and word of mouth influence customer decisions in choosing JNE delivery services at the Medan branch.  Purchase intention, in this context, refers to the desire to use the service. The research used quantitative methods with Ordinary Least Square (OLS) and involved primary and secondary data from 100 respondents selected by chance. Analysis was carried out using SPSS 23. Based on the description of the respondent profiles, there were 38 men (38%) and 62 women (62%). In terms of age, there were 11 respondents under 20 years of age, while the 20-25 year age group was the largest with 45 people. The 26-30 year age group consists of 30 people, and those aged over 30 years consist of 14 people. The main occupation of respondents who use JNE Medan Marelan Branch services is dominated by 40 employees, followed by 30 students, 11 self-employed people, and 19 others (including those who have not worked, not working, domestic workers) of the total number of respondents, 65 people have used JNE Medan Marelan services more than 5 times, while 35 people have used these services less than 5 times. Findings show that individual company image does not have a significant effect on intention to use, while service quality and word of mouth has a significant positive influence. Overall, these three factors have a significant impact on interest in using services. The Adjusted R Square value is 0.517, indicating that 51.7% of interest in using JNE is influenced by these three variables, while 48.3% is influenced by other factors not studied.